CIRCADIAN GENES AND REGULATION OF DIAPAUSE IN INSECT - Bajgar, Adam (Jihočeská univerzita, 2013)
This thesis considers various roles of circadian clock genes in insect physiology. Application of molecular-biology methods in Pyrrhocoris apterus, non-model insect species, enable us to investigate involvement of circadian clock genes in photoperiod induced physiological responses. We discover involvement of neuroendocrine cells, and a role of Juvenile hormone (JH) signalization in transduction of photoperiodic signalization to peripheral tissues. We found new principles of JH signal diversification in tissue specific manner, and in addition described molecular mechanism of photoperiod induced changes in gut physiology. Comparison of gut and fat body tissue reveals that mechanism observed in the gut is tissue specific, and that circadian clock genes exhibit tissue specific functional pleiotropic effect.
CIRCADIAN GENES AND REGULATION OF DIAPAUSE IN INSECT
Keywords: Circadian clock genes; cry; Pdp; diapause induction; JH signalization; ovary development; Photoperiod